The Use Of Story - Mapping Technique In Teaching Reading Skill At The Second Year Of SMP Muhammadiyah 6 Surakarta In 2014/2015 Academic Year - Prakusumasari, Kukuh; , Drs. Djoko Srijono, M.Hum; , Nur Hidayat, M.Pd (2015)
The objectives of this research are to describe the procedure of teaching reading by using story mapping technique and to identify the result of story mapping technique in reading comprehension of narrative text. The research was done to the second year students of SMP Muhammadiyah 6 Surakarta. As the sample, the researcher took 30 students of VIIIA class and chose 5 students randomly. The data were collected from the observation in the classroom and interview with the English teacher and also the VIIIA class of the second year students of SMP Muhammadiyah 6 Surakarta. After collecting the data and analyzing them, the researcher describes the research finding. Teaching using story mapping technique was conducted in four meetings. It is appropriate in reading teaching-learning of narrative text and helps the students to develop their reading skill. There are some result, The story mapping technique gives positive impact to the success of teaching reading of narrative text. Story mapping technique helps the students to comprehend the content of narrative text easily. Story mapping technique helps them remembering the important content of reading narrative text. The students are able to analyze the generic structure of the text. They are more interested in joining teaching-learning activities, the students have development of reading skill.